Absent right superior vena cava and persistent left superior vena cava: An incidental finding - Swati Joshi; Ajmer Singh (Annals of Cardiac Anaesthesia, 2023)
A patient with Marfan syndrome undergoing Bentall operation was found to have an absent right superior vena cava and persistent left superior vena cava. The dilation of coronary sinus raised the suspicion of persistent left superior vena cava. The diagnosis was confirmed by agitated saline contrast echocardiography and computed tomography of the chest.